PERAN DAN TANGGUNG JAWAB NOTARIS TERHADAP PELAKSANAAN PENDAFTARAN BADAN HUKUM PERSEROAN TERBATAS MELALUI SISTEM ONLINE - Erina Permatasari; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The aims of this research were to looking for and analyzing: 1) Company registration procedure by online sysem, 2) Notary’s role and responsibility in the company registration by online system, if had error inputing data, 3) the law effect of notary’s role and responsibility if had been error inputing data, from UU ITE sight and 1365 KUHPerdata chapter sight. Data using was primary data, secoundary and tersier as supporting data, and then analized by quantitative-descriptive methode.Based on nalizing result had some conclusion that: 1) Registratin company procedure by online system that in generally beginning from company name order and been follow up with making the companies act as the SABH forms in electronics by notary. If the data input was complete and right also had been agree by Law and human Right Ministery so been had Decission Letter of law entity legalacyby Minister. 2) Role of the notary in company registration with online system was since client ask to registration the company until Decission Letter of law entity legalacyby Minister was out. The notary responsibility if done guilty like error inputing data, no related with UU ITE because no chapter about, but with 1365 BW chapter where doing of error inputing data was harming another person so hane to re the harmed with repairing the data and make act changing. Keywords: Notary, Company Resgistration, Online